The Information in the Origin and development of the Documentation - López Yepes, José (JLIS.it, 2015)
The contribution of José López Yepes has as main purpose to propose a reflection on the fundamentals of the Documentation, the Library and Information Science in a time of great changes and the loss of many landmarks. According to the scholar we must start from the study of the concepts of information and documents and their close relationship. The message, says Yepes, is transmitted through the document in space and time and so in turn become an important source of information. Information is therefore the core and foundation of documentation and related disciplines, although it can not be considered an exclusive object of their study. We must then go back to think about the document, and in particular on its nature, since it is a necessary starting point for scholars of the subject. The author, in this article, in addition to signaling the need for a theoretical study aims to rediscover the work of Paul Otlet and in particular the Traité de Documentation (1934). The aim is not simply to pay tribute to the founder of modern documentation, but to invite to recognize the relevance of a thought that still can make an important contribution to the redefinition of key concepts of the discipline.